On the use of Disease Staging for clinical management: analysis of untimely admissions in the Abruzzo Region, Italy (Italian Journal of Public Health, 2004)
Background and aims. The process of decentralization which recently occurred within the Italian National Health Service has transferred substantial responsibility and authority for health care administration to the individual regions. The project is aimed at developing regional benchmarks that can be used as a part of an ongoing system for analysis of resource use and quality of care in the Abruzzo Region of Italy.Methods. All 286 924 hospital admissions for the year 2001 in the region were analysed. Three diseases were chosen for in-depth review: diabetes mellitus; cholecystitis/cholelithiasis; and bacterial pneumonia. There were a total of 9391 admissions for these diagnoses. Severity, length of hospital stay and hospital mortality were analysed using Disease Staging methodology. In addition, the timeliness of hospitalisation was assessed by grouping admissions in three categories: premature or medically unnecessary, timely and late.Results. The rate of medically unnecessary admissions for diabetes mellitus was 72% throughout the region, and the percentage of late hospitalisations for cholelithiasis/cholecystitis was 43%. For both diseases, there were significant variations across Local Health Units in the proportion of late and early admissions. The rate of timely hospitalisations for bacterial pneumonia was higher than 86%.Conclusion. The analysis of discharge abstract data using Disease Staging revealed that in the Abruzzo region there are problems of inappropriate hospital admission, both early and late, for all diseases examined excepted bacterial pneumonia.Data confirmed the validity of Disease Staging to compare the performance of diverse hospitals in terms of length of stay and in-hospital mortality.
Keywords: health care management; disease staging; timeliness; hospitalisations; Italy